2003
DOI: 10.4269/ajtmh.2003.69.341
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Meningoencephalitis Due to Toxocara Canis: Case Report and Review of the Literature

Abstract: Toxocariasis is usually manifested as visceral larva migrans. Nervous system involvement is a rare complication. In this report, we describe one case of meningoencephalitis due to Toxocara canis and review the literature. We report a previously healthy two-year-old boy who was admitted after 24 hours of severe neurologic symptoms with marked eosinophilic pleocytosis in the cerebrospinal fluid and a single subcortical lesion detected by cerebral magnetic resonance imaging. Both serum and spinal fluid tested pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 20 publications
0
69
0
6
Order By: Relevance
“…Eosinophil blood counts are highly elevated in majority of patients having high IgG titres, but in the case of ocular toxocariasis, eosinophilia is present only in 10 -15 % of patients (Gillespie et al, 1993). Only very rarely eosinophilia can be found in the cerebrospinal fluid (Vidal et al, 2003). MRI examination of our patient revealed multifocal hypo-intense lesions on T1 weighted image and hyper-intense signal on T2 type of images, where confluent pattern with diameter up to 1 -2 cm was observed.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Eosinophil blood counts are highly elevated in majority of patients having high IgG titres, but in the case of ocular toxocariasis, eosinophilia is present only in 10 -15 % of patients (Gillespie et al, 1993). Only very rarely eosinophilia can be found in the cerebrospinal fluid (Vidal et al, 2003). MRI examination of our patient revealed multifocal hypo-intense lesions on T1 weighted image and hyper-intense signal on T2 type of images, where confluent pattern with diameter up to 1 -2 cm was observed.…”
Section: Discussionmentioning
confidence: 83%
“…Cerebral Toxocara infections in humans are rare and the clinical pattern of neurotoxocariasis may be that of eosinophylic meningitis, encephalitis, myelitis, seizures, vasculitis or isolated behavioral changes (Vidal et al, 2003;Marx et al, 2007). A young woman diagnosed for neurotoxocariasis (Mizuki et al, 1985) suffered from se- vere eosinophylic meningitis and the authors suggested that the serious course of the disease was due to the immunodeficiency caused by parallel rubella infection.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases these larvae may migrate to the central nervous system where they may cause a constellation of neurological symptoms, including meningoencephalitis, focal deficits and seizures. 3,4 Studies have estimated seroprevalence in humans to be between 35%-42% in hot and humid agricultural regions (2%-5% in urban areas) of more economically developed countries, and even higher in less economically developed countries. 5 In one study conducted in Turkey, toxocara seroprevalence was much higher in schizophrenic patients (45.9%) than in the general population (2%).…”
Section: Toxocaramentioning
confidence: 99%
“…Both methods detect specifi c IgG. For neurological toxocariasis, immunodiagnosis can be carried out on CSF [78].…”
Section: Diagnosis Of Human Toxocariasismentioning
confidence: 99%
“…The parasite burden is always tiny and often reduced to one larva; thus an immunodiagnostic test carried out on serum usually is negative [78]. For ocular toxocariasis, immunodiagnosis is made possible using Aqueous Humor (AH) in a TES-ELISA [79] or WB [80].…”
Section: Diagnosis Of Human Toxocariasismentioning
confidence: 99%